Teacher education at the edge : expanding access and exploring frontiers - Huber, Tonya; O'Meara, James (Emerald Publishing Limited : Information Age Publishing, Inc., 2019)
"International Education Inquiries is a book series dedicated to realizing the global vision of Education 2030a. This vision involves "ensuring inclusive and equitable quality education and promoting lifelong learning opportunities for all." The founding editors seek to provide a forum for the diverse voices of scholars and practitioners from across the globe asking questions about transforming the vision of Education 2030 into a reality. Published chapters will reflect a variety of formats, free of methodological restrictions, involving disciplinary as well as interdisciplinary inquiries. We expect the series will be a leading forum for pioneers redefining the global discussion about the people, places and perspectives shaping Education 2030 outcomes. Education 2030 topics of interest include, but are not limited to Improving access to quality early childhood development, care and pre-primary education. Ensuring equal access for all women and men to affordable and quality education. Increasing the number of youth and adults who have skills relevant for sustainable living and livelihoods. Ensuring equal access for the vulnerable, including persons with disabilities, indigenous peoples and children in vulnerable situations. Achieving levels of literacy and numeracy required to engage in communities and employment Acquiring the knowledge and skills needed to promote sustainable development, including: education for sustainable development and sustainable lifestyles, human rights, gender equality, promotion of a culture of peace and non-violence, global citizenship education, and the appreciation of cultural diversity and of culture's contributions to sustainable development. Providing safe, non-violent, inclusive and effective learning environments for all. Recruiting, preparing, supporting and retaining quality teachers"-- Provided by publisher.
Keywords: Teachers -- Training of.; Education and globalization.; Inclusive education.; Educational equalization.; Sustainable development.; Education -- Teacher Training & Certification.; Teacher training.; elektronické knihy; electronic books